2012
DOI: 10.3857/roj.2012.30.3.99
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictive factors of pathologic tumor response after preoperative chemoradiotherapy in rectal cancer

Abstract: PurposeThe aim of this study was to identify clinical predictive factors for tumor response after preoperative chemoradiotherapy (CRT) in rectal cancer.Materials and MethodsThe study involved 51 patients who underwent preoperative CRT followed by surgery between January 2005 and February 2012. Radiotherapy was delivered to the whole pelvis at a dose of 45 Gy in 25 fractions, followed by a boost of 5.4 Gy in 3 fractions to the primary tumor with 5 fractions per week. Three different chemotherapy regimens were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…Recent studies have suggested that the radiosensitivity was not only depend on the biological characteristics of tumor cells, but also being affected by tumor microenvironment (Barcellos-Hoff et al, 2005), which gave us the inspiration that the blood cells, as part of the microenvironment, might play a critically important role for tumor regression after nCRT in patients with LARC. In fact, some results have clearly shown that circulating lymphocyte levels were significantly different in CR patients and non-CR patients (Kitayama et al, 2011;Choi et al, 2012). But to our knowledge, the report that circulating lymphocyte can predict TRG to nCRT in rectal cancer was rare.…”
Section: Figure 1 Impact Of Pretherapeutic Lymphocyte Ratio On 5-yeamentioning
confidence: 82%
“…Recent studies have suggested that the radiosensitivity was not only depend on the biological characteristics of tumor cells, but also being affected by tumor microenvironment (Barcellos-Hoff et al, 2005), which gave us the inspiration that the blood cells, as part of the microenvironment, might play a critically important role for tumor regression after nCRT in patients with LARC. In fact, some results have clearly shown that circulating lymphocyte levels were significantly different in CR patients and non-CR patients (Kitayama et al, 2011;Choi et al, 2012). But to our knowledge, the report that circulating lymphocyte can predict TRG to nCRT in rectal cancer was rare.…”
Section: Figure 1 Impact Of Pretherapeutic Lymphocyte Ratio On 5-yeamentioning
confidence: 82%
“…Recently, multiple studies have shown the association between the conventional treatment using certain anticancer agents and immune responses against cancer cells . Based on these results, significant numbers of researchers now appear to believe that chemotherapeutic agents can induce anti‐tumor immune responses that significantly contribute to the overall anti‐tumor effects of the chemotherapeutic agents .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple studies have shown the association between the conventional treatment using certain anticancer agents and immune responses against cancer cells. (18)(19)(20)(21)(22)(23) Based on these results, significant numbers of researchers now appear to believe that chemotherapeutic agents can induce anti-tumor immune responses that significantly contribute to the overall anti-tumor effects of the chemotherapeutic agents. (24) Our results presented here appear to support this notion and suggest that the PD-1 system might be one of the key players in determining the chemotherapy-related immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) is an established tumor marker and has demonstrated its prognostic value in colorectal cancer (4). CEA is also overexpressed in approximately 35-60% of patients with NSCLC (5), and the clinical usefulness of the serum CEA level in lung cancer has recently been vigorously explored.…”
Section: Original Articlementioning
confidence: 99%